Case report: Substantial improvement of autism spectrum disorder in a child with learning disabilities in conjunction with treatment for poly-microbial vector borne infections - Offutt, Amy; Breitschwerdt, Edward B. (Frontiers in Psychiatry, 2023)
Poly-microbial vector-borne infections may have contributed to neuropsychiatric symptoms in a boy diagnosed with autism spectrum disorder. Targeted antimicrobial treatment resulted in substantial improvement in cognitive (such as learning disabilities, focus, concentration) and neurobehavioral (such as oppositional, defiant, anti-social, disordered mood, immaturity, tics) symptoms.